The Impact of Communication Factors on Job Satisfaction Among Icelandic Employees in the Public Sector - Jóhannes Þorkelsson 1994- (2018)
The main purpose of the present study was to explore the impact of communicative factors on job satisfaction and employee’s desired need for new ways of communicating. In addition, it was assessed whether communicative factors would differ between employees that had any subordinates and those who did not. Participants in the study were 127 employees in leisure centers in Reykjavik, Iceland. A survey was conducted and consisted of nine factors measuring role expectations, leadership, justice, social support, and job satisfaction. Regression analysis revealed a significant relationship between employee’s job satisfaction and interactional justice, procedural justice, role clarity, role conflict, empowering leadership, fair leadership, support from co-workers, and support from superiors which supports the primary hypothesis. Results also provided support to the secondary hypothesis as employees desired need for new methods of communication was significantly related to role conflict and interactional justice. T-test analysis revealed that those who had any subordinates experienced more empowering leadership, more procedural justice and more role clarity in the workplace than those who did not have subordinates. This study supports the importance of developing new methods that encourage fairness in order to increase job satisfaction. Keywords: organizational psychology, job satisfaction, communication, organizational justice, social support, leadership, role expectations Þessi rannsókn var framkvæmd til þess að kanna áhrif samskiptaþátta á starfsánægju og þörf starfsmanna á nýjum leiðum til þess að eiga samskipti á vinnustöðum. Til viðbótar var kannað hvort þessir samskiptaþættir væru ólíkir milli starfsmanna sem höfðu undirmenn og þeirra sem höfðu enga undirmenn. Spurningalisti var sendur á 350 starfsmenn og voru 127 starfsmenn í frístundamiðstöðvum og félagsmiðstöðvum í Reykjavík sem svöruðu. Spurningalistinn innihélt mælingar á níu þáttum; hlutverkum og væntingum, stjórnun, félagslegum stuðning, réttlæti og ...